鼓形蛇簧联轴器的设计与性能分析 - 曾鹏修; 陈光柱; 黄虎 (Jixie chuandong)
Serpentine spring coupling,as a flexible coupling is widely used in general machinery occasions.A novel serpentine spring coupling-the drum serpentine spring coupling is presented.Firstly,the mechanics modeling of the serpentine spring is built,and the statics analysis of the drum serpentine spring coupling is carried out by using the finite element simulation software-ANSYS 12.0Workbench.The results show that the maximum stress value of the drum serpentine spring coupling is smaller than of the latest arc-shaped serpentine spring coupling by the results of static analysis.Finally,the torsional stiffness impact factors of the drum serpentine spring coupling are attained by the torsional stiffness theoretical analysis.